Molecular Docking as a Therapeutic Approach for Targeting Cancer Stem Cell Metabolic Processes - Arjmand, Babak; Hamidpour, Shayesteh Kokabi; Alavi-Moghadam, Sepideh; Yavari, Hanieh; Shahbazbadr, Ainaz; Tavirani, Mostafa Rezaei; Gilany, Kambiz; Larijani, Bagher (Frontiers in Pharmacology, 2022)
Cancer stem cells(CSCs) are a subpopulation of cells which are involved in cancer initiation, progression, and development. They display resembling characteristics to natural stem cells such as self-renewal, survival, differentiation, proliferation, and quiescence. Moreover, they have some characteristics that eventually can demonstrate the heterogeneity of cancer cells and tumor progression. Another aspect of CSCs that has been recognized as a central concern facing cancer patients is resistance to mainstays of cancer treatment. Owing to these details these immature progenitors of cancerous cells can constantly persist after different therapies and cause tumor regrowth or metastasis. In both normal development and malignancy, cellular metabolism and stemness are intricately linked and CSCs dominant metabolic phenotype changes across tumor entities, patients, and tumor subclones. In this context, researchers are searching out new alternative or complementary therapies such as targeted methods to fight against cancer. Molecular docking is one of the computational modeling methods that have a new promise in cancer cell targeting through drug designing and discovering programs. As a comprehensive approach, this computational drug design method can be thought more cost-effective and time-saving compare to other conventional methods in cancer treatment. In addition, increasing productivity and quality in pharmaceutical research can be another advantage of this molecular modeling method. Therefore, in recent years, it can be concluded that molecular docking can be considered as one of the novel strategies at the forefront of the cancer battle via targeting cancer stem cell metabolic processes.